A solvent-free UV curing pressure-sensitive adhesive and preparation method thereof
By using solvent-free UV curing pressure-sensitive adhesive in polarizers, the problems of solvent pollution, low production efficiency and insufficient heat resistance in the prior art are solved, and efficient and environmentally friendly polarizer production is achieved.
Patent Information
- Application Number
- CN202510245324.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The pressure-sensitive adhesives of existing polarizers have problems such as solvent volatile pollution, low production efficiency, and insufficient heat resistance, which is difficult to meet the demand for high-quality image display of liquid crystal displays.
Solvent-free UV curing pressure-sensitive adhesives are used, including liquid polyurethane acrylate, active diluents, antistatic agents and photoinitiators, to form a viscose layer through UV photocuring to improve bonding and moisture-heat resistance.
It achieves excellent bonding, humidity and heat resistance and heat aging resistance, reduces environmental pollution, improves production efficiency and product quality.
Smart Images

Figure CN119736060A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of optical films, and in particular to a solvent-free UV curing pressure-sensitive adhesive applied to polarizers and a preparation method thereof. Background Art
[0002] Modern liquid crystal displays require the polarization effect of polarizers to display high-quality images, so polarizers are one of the most core components in liquid crystal displays. The composition of polarizers includes: a functional polyvinyl alcohol layer (PVA) in the middle that plays a polarizing role, a triacetyl cellulose layer (TAC) film, an acrylic film or a cycloolefin polymer film that plays a protective role on both sides, and a PET film with a pressure-sensitive adhesive applied on one side, and a pressure-sensitive adhesive is applied on the release film and adhered to the other side after drying. When using, the polarizer can be easily attached to the device by removing the release film. The PVA film of the polarizer and the iodide in it are extremely easy to absorb moisture, and are easy to deform and shrink at high temperatures, resulting in stress between the pressure-sensitive adhesive and the display glass plate, causing problems such as warping, bubbles, delamination and peeling of the polarizer.
[0003] In addition to suitable initial adhesion, long-term adhesion and good optical properties, the pressure-sensitive adhesive of polarizers also needs good moisture resistance, heat aging and re-peeling properties. The solvent-based heat-crosslinked acrylic pressure-sensitive adhesive currently used in domestic polarizers has the following obvious problems: volatile pollution of solvents and carbon dioxide emissions generated by burning solvents; the solvent volatilization process limits the production efficiency of polarizers, and long-term heating at high temperatures will affect the flatness and quality of polarizers; the two-component pressure-sensitive adhesive liquid with aziridine as the crosslinking agent has a short storage time and is prone to gelation failure and waste; the thermal crosslinking agent remaining in the pressure-sensitive adhesive layer reduces the thermal stability and weather resistance of the acrylic pressure-sensitive adhesive, causing problems such as poor polarizer lamination.
[0004] The use of UV curing pressure sensitive adhesive can overcome the above-mentioned shortcomings of solvent-based pressure sensitive adhesive, but the current acrylate UV pressure sensitive adhesive has insufficient heat resistance when used for polarizers. For example, when a polarizer coated with acrylate UV pressure sensitive adhesive is attached to a glass plate, warping, debonding, and debonding occur at the bonding edge when stored at 80°C. Therefore, a UV pressure sensitive adhesive with better heat resistance is needed for advanced production processes of polarizers. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the present invention provides a solvent-free UV curable pressure-sensitive adhesive for polarizer and a preparation method thereof. In a first aspect, the present application provides a solvent-free UV-curable pressure-sensitive adhesive for a polarizer, comprising the following components by weight percentage: Liquid polyurethane acrylate 50~70%; Active diluent 30~47%; Antistatic agent 1.5~2%; Photoinitiator 0.3-1%; The liquid polyurethane acrylate is prepared by polymerization of polyoxypropylene diol, aliphatic diisocyanate and hydroxyl-containing acrylate; The mass ratio of -OH groups in the polyoxypropylene diol to -NCO groups in the aliphatic diisocyanate is 0.5-1, and the viscosity of the liquid polyurethane acrylate is 40 Pa.s-300 Pa.s; The concentration of acrylate functional groups in the liquid polyurethane acrylate is less than 0.1 mmol / g.
[0006] More specifically, the mass ratio of the -OH group in the polyoxypropylene diol to the -NCO group in the aliphatic diisocyanate is 0.75-0.87, and the viscosity of the liquid polyurethane acrylate is 60 Pa.s-250 Pa.s.
[0007] More specifically, the concentration of acrylate functional groups in the liquid polyurethane acrylate is 0.05-0.09 mmol / g.
[0008] More specifically, the liquid polyurethane acrylate is prepared by polymerization of polyoxypropylene glycol, polytetramethylene glycol, aliphatic diisocyanate and hydroxyl-containing acrylate.
[0009] More specifically, the aliphatic diisocyanate is selected from any one of hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane-4,4'-diisocyanate.
[0010] More specifically, the hydroxyl-containing acrylate is selected from any one of hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxybutyl acrylate.
[0011] More specifically, the active diluent is a monofunctional active diluent selected from one or more of acrylate, vinyl amide and acrylamide.
[0012] More specifically, the photoinitiator is a free radical photoinitiator that is sensitive to UV light of 250-400 nm.
[0013] In a second aspect, the present application provides a method for preparing a solvent-free UV-curable pressure-sensitive adhesive, the specific steps of which are: by weight percentage, liquid polyurethane acrylate, reactive diluent, antistatic agent and photoinitiator are fully mixed to obtain a solvent-free UV-curable pressure-sensitive adhesive.
[0014] In a third aspect, the present application provides a polarizer, which includes, from top to bottom: a functional layer, an upper PVA protective film, a PVA polarizer, a lower PVA protective film, a solvent-free UV-curable pressure-sensitive adhesive layer, and a release film.
[0015] To be more specific, the display of LCD requires two layers of polarizers with different polarization degrees to be orthogonal, and then the liquid crystal is powered on and deflected to display the image. For example, 0-degree and 90-degree polarizers can be selected for orthogonal connection, and the upper PVA layers of the 0-degree polarizer and the 90-degree polarizer have functional differences. Various functional coatings are provided on the upper PVA protective film layer of the 0-degree polarizer, and the functional layer includes at least one of the functions of anti-glare function, anti-reflection function, anti-scratch function, and wide viewing angle diffusion function. The functional layer can also be a coating with a haze of 0.1~27%, an anti-glare coating, an anti-reflection coating, a low-reflection coating, a high-hardness anti-scratch coating, and a wide viewing angle diffusion coating. The functional layer can have several of these characteristics. The substrate of the upper PVA protective film can be any one of triacetyl cellulose (TAC), acrylic resin film (PMMA), and polyethylene terephthalate (PET). The PVA protective film layer on the 90-degree polarizer can also be selected from any one of triacetyl cellulose (TAC), acrylic resin film (PMMA), and polyethylene terephthalate (PET), but generally has no functional coating, but some filter materials UV absorbers are added to absorb the light band 415~460nm that is irritating to the human eye. More specifically, the lower PVA protective film is selected from any one of triacetyl cellulose (TAC) with a phase compensation value or triacetyl cellulose with a phase compensation value of 0, cyclopentadiene film (COP), and acrylic film with a phase compensation value of 0.
[0016] More specifically, the release film has extremely low surface energy and does not bond with the pressure-sensitive adhesive. The release film is selected from any one of a PET film, a BOPP film, and a PE film. The thickness of the release film is 0.025 to 0.060 mm.
[0017] More specifically, the PVA polarizer is a film-forming polyvinyl alcohol, which can be swollen and stretched in water, and can attach iodine ions in an iodine solution, thereby achieving dichroic selective absorption of light.
[0018] Specifically, when the solvent-free UV curable pressure sensitive adhesive designed in the present application is UV cured, the irradiation dose of the UV curing light source is 600-1500 mJ / cm 2 .
[0019] More specifically, after the solvent-free UV-curable pressure-sensitive adhesive is UV-cured, the Tg of the pressure-sensitive adhesive is lower than 10° C. and higher than -25° C.
[0020] Beneficial effects of the present invention: 1) The solvent-free UV curable pressure-sensitive adhesive designed by the present invention has excellent bonding and moisture and heat resistance and heat aging resistance performance, and has no solvent emission during production and use, and is environmentally friendly, green and pollution-free.
[0021] 2) The production of polarizers with solvent-free UV-curable pressure-sensitive adhesives is more energy-saving and environmentally friendly than solvent-based acrylate and water-based acrylate pressure-sensitive adhesives, has low carbon emissions and is easy to mass-produce.
[0022] 3) The pressure-sensitive adhesive is cured using UV light. Compared with the lengthy oven and high-energy-consuming and complex air intake and exhaust systems used for thermosetting pressure-sensitive adhesives, the UV irradiation device has a simple structure, low production cost and high production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a schematic diagram of the structure of a polarizer including a solvent-free UV-curable pressure-sensitive adhesive layer in the present application; Figure 2 It is a schematic diagram of solvent-free UV curing pressure-sensitive adhesive coating in this application.
[0024] In the figure: 1. Functional layer; 2. Upper PVA protective film; 3. PVA polarizer; 4. Lower PVA protective film; 5. Solvent-free UV-curable pressure-sensitive adhesive layer; 6. Release film. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the specific implementation methods of the present invention are clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The solvent-free UV curing pressure-sensitive adhesive designed by the invention comprises the following components in percentage by weight: 50-70% of liquid polyurethane acrylate, 30-47% of active diluent, 1.5-2% of antistatic agent and 0.3-1% of photoinitiator.
[0027] The viscosity of liquid polyurethane acrylate (PUA) is greater than 40Pa.s and less than 300Pa.s, and the glass transition temperature Tg is lower than 0°C. PUA is polyurethane (PU) chemically modified with acrylate, and the acrylate functional group is at the end of the PU molecular chain. Liquid polyurethane acrylate can be synthesized by polymerization of polyoxypropylene glycol (PPG), aliphatic diisocyanate and hydroxyl-containing acrylate. The molecular weight of PPG is between 1000-4000g / mol, and the preferred molecular weight is 3000-4000g / mol. An appropriate amount of polytetramethylene glycol (PTHF) can also be further added to the polymerization reaction, that is, PUA can also be synthesized by polymerization of PPG, PTHF, aliphatic diisocyanate and hydroxyl-containing acrylate.
[0028] In some specific embodiments, the aliphatic diisocyanate is selected from any one of hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane-4,4'-diisocyanate. The hydroxyl-containing acrylate is selected from any one of hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxybutyl acrylate.
[0029] In the synthesis process of liquid polyurethane acrylate, the viscosity of polyurethane acrylate can be regulated by regulating the mass ratio of the hydroxyl group in polyoxypropylene diol and the isocyanate group in the aliphatic diisocyanate. In this application, the -OH / -NCO ratio is designed to be between 0.5 and 1. When the ratio is close to 0.5, the molecular weight of the resin is small and it is not suitable as a pressure-sensitive adhesive resin; when the OH / NCO ratio is close to 1, the molecular weight and viscosity of the resin increase rapidly, and it is not suitable as a pressure-sensitive adhesive resin. This application controls the viscosity of the PUA resin within the range of 40Pa.s to 300Pa.s by controlling the OH / NCO ratio. Further preferably, in order to achieve better results, the OH / NCO ratio is controlled between 0.75 and 0.87, and the viscosity of the PUA is controlled within the range of 60Pa.s to 250Pa.s.
[0030] The concentration of acrylate functional groups in liquid polyurethane acrylate is less than 0.1 mmol / g, and more preferably, the concentration of acrylate functional groups is between 0.05 and 0.09 mmol / g. The concentration of acrylate functional groups is controlled by adjusting the amount of hydroxyl-containing acrylate added and the appropriate NCO concentration to take into account the activity during UV curing, the performance of the pressure-sensitive adhesive, and the viscosity of the prepared adhesive. The mass proportion of PUA resin in the adhesive is greater than 50%, but preferably less than 70%.
[0031] The reactive diluent is a monofunctional reactive diluent, which is used to adjust the viscosity of the solvent-free UV pressure-sensitive adhesive and the performance of the pressure-sensitive adhesive after UV curing. The reactive diluent includes acrylates, vinylamides or acrylamides containing alicyclic rings, aromatic rings, alkyl groups or polar functional groups, such as -O-, -OH, -COOH. The monofunctional reactive diluent is selected from one or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, acrylate norbornyl ester, phenoxyethyl acrylate, diethoxyethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, methacrylic acid, acrylic acid, acryloyl morpholine, N,N-dimethylacrylamide, and N-vinyl pyrrolidone. Acrylates with less odor are preferred, such as alkyl acrylates with an alkyl carbon atom number greater than 4, diethoxyethyl acrylate, hydroxy acrylate, acryloyl morpholine, N,N-dimethylacrylamide, and the like. When using PUA resin with lower viscosity, the active diluent should contain active diluents with polar groups, such as hydroxy acrylate, methacrylic acid, acrylic acid, acrylamide, N,N-dimethylacrylamide, NVP, etc., to increase the cohesive energy of the pressure-sensitive adhesive. The selection and dosage of active diluents are related to the viscosity of the PUA resin. The higher the viscosity of the resin, the more diluent should be used, and the less polar monomer can be used, and vice versa. The viscosity of the glue solution suitable for coating is usually 2~15Pa.s, which is also related to the coating equipment and coating process. The amount of active diluent added can be determined through experiments.
[0032] In some specific embodiments, the antistatic agent can be selected from ionic or nonionic antistatic agents, such as quaternary ammonium salts, phosphates, fatty acid polyol esters and ionic liquid antistatic agents, with a mass ratio of 1.5-2%. Adding an antistatic agent can reduce the surface resistance of the pressure-sensitive adhesive coated on the surface of the polarizer, inhibit surface static electricity, prevent safety accidents caused by static electricity, and make it easier and smoother to attach the polarizer to the glass. The photoinitiator selects a free radical photoinitiator that is sensitive to UV light of 250-400nm. The photoinitiator can be selected from various types of commercially available aromatic alkyl ketones, α-hydroxy ketones, acylphosphine oxides and their derivatives, various oxime esters, etc., for example: OXE series oxime esters such as 1173, 184, 2959, 907, 369, 819, TPO, OXE-1 and OXE-2, and the mass proportion of the photoinitiator in the solvent-free glue is 0.3-1%.
[0033] The present application also provides a method for preparing a solvent-free UV curable pressure-sensitive adhesive: liquid polyurethane acrylate, reactive diluent, antistatic agent and photoinitiator are fully mixed uniformly by weight.
[0034] When the solvent-free UV curable pressure-sensitive adhesive designed in the present application is used, the curing light source is irradiated with a UV light source of 250-400nm. In some specific embodiments, the UV light source is selected from a light source that can radiate 280-410nm light waves such as a mercury lamp, UV-LED, laser, pulse flash, or a combination of light sources, preferably a combination of a mercury lamp and a UV-LED lamp. The irradiation dose is preferably 600-1500mJ / cm 2 .
[0035] UV light source irradiation stimulates the decomposition of the photoinitiator, generates free radicals, causes the double bonds of the acrylate in the glue to polymerize quickly, crosslink and solidify, and forms an adhesive layer with pressure-sensitive properties. The thickness of the glue coating can be 10~35μm, preferably controlled at 20~30μm, which can have better pressure-sensitive adhesive properties.
[0036] The glass transition temperature (Tg) of the solvent-free UV pressure-sensitive adhesive after UV curing is lower than 10°C and higher than -25°C, and the visible light transmittance is >90%; the peeling force on glass is greater than 200gf / 25mm, and the peeling force on release film is less than 12 gf / 25mm.
[0037] The present application also provides a polarizer, such as Figure 1 As shown, from top to bottom, it includes: functional layer, upper PVA protective film, PVA polarizer, lower PVA protective film, solvent-free UV curing pressure-sensitive adhesive layer, and release film. Covering the release film on the surface of the pressure-sensitive adhesive layer can isolate the air, so that the free radical polymerization reaction can proceed better, produce a better polymer cross-linking network, and have better pressure-sensitive adhesive performance. The release film covering the adhesive liquid needs to be transparent and of appropriate thickness, and can completely cover the adhesive liquid. PE film, OPP film, and PET film with a thickness of 0.02~0.06mm can be selected, and PET film with a thickness of 0.02-0.06mm is preferred.
[0038] In some specific embodiments, the upper PVA protective film and the lower PVA protective film can be selected from any one of a triacetyl cellulose (TAC) film layer, a polymethyl methacrylate (PMMA) film layer, and a polyolefin film layer. The materials of the upper PVA protective film and the lower PVA protective film can be the same or different. The lower PVA protective film can be selected from a film material with a phase compensation value or a film material without a phase compensation value (the phase compensation value is 0).
[0039] like Figure 2As shown, the coating method of the solvent-free UV pressure-sensitive adhesive designed by the present application can adopt a double-roll coating method, using a coating roller and a backing roller, using the coating roller to carry the pressure-sensitive adhesive from the coating tank, and transferring part of the pressure-sensitive adhesive to the polarizer to be coated running between the coating roller and the backing roller. This method can evenly coat the pressure-sensitive adhesive on the polarizer. By adjusting and selecting the composition and proportion of the above-mentioned resin and active diluent, the UV-cured pressure-sensitive adhesive has good adhesion to these films.
[0040] After the polarizer with pressure-sensitive adhesive is attached to the glass, an aging test is performed: After aging test at 80℃ for 500 hours, no appearance changes such as bubbling, peeling, and glue cracking were observed; After 300 cycles of aging test at -35℃ (30 minutes) and 80℃ (30 minutes), no significant appearance changes such as blistering, peeling, glue cracking and discoloration were observed, and the temperature change test was passed; After aging test for 500 hours at 60℃ and 90% humidity, no appearance changes such as bubbling, peeling, glue cracking and discoloration were observed, and the test of temperature and humidity changes was passed.
[0041] <Formula Material Description>: In the following specific examples and comparative examples, polyurethane acrylate (PUA) is synthesized from polyphenylene ether (PPO), polytetramethylene glycol (PTHF), isophorone diisocyanate (IPDI) and hydroxypropyl acrylate (HPA), and the viscosity of the synthetic resin is adjusted by adjusting the -OH / -NCO ratio, wherein: The viscosity of PUA-1 at 30°C was 230 Pa.s, and the content of acryloyloxy groups was 0.1 mmol / g; The viscosity of PUA-2 at 30°C was 120 Pa.s, and the content of acryloyloxy groups was 0.07 mmol / g; The viscosity of PUA-3 at 30°C is 60 Pa.s, and the content of acryloyloxy groups is 0.05 mmol / g; A mixture of 10% by mass of butyl acrylate and 1% of photoinitiator 184 was added to the synthetic resin. After UV light curing, the glass transition temperatures TG were measured to be -30°C, -35°C and -45°C respectively.
[0042] The active diluent is selected from one or more of isooctyl acrylate, norbornyl acrylate (IBOA), tetrahydrofuran acrylate (THFA), methacrylic acid (MA), and acryloyl morpholine (ACMO). The photoinitiator is TPO, and the antistatic agent is Pebax® polymer antistatic agent from Arkema.
[0043] The options for polarizer substrates are: Substrate 1: A polarizer substrate with an upper protective film layer and a lower protective film layer being PMMA; Substrate 2: The upper protective film layer and the lower protective film layer are TAC polarizer substrates.
[0044] <Performance Test Description> The viscosity of the resin and the adhesive in the following embodiments and comparative examples was measured by a modular intelligent advanced rotational rheometer; the glass transition temperature was measured by a differential scanning calorimeter (DSC) at a heating rate of 10°C / min; the pressure-sensitive adhesive was cut into 25×250 mm strips, attached to glass, and the 180° peel force was measured by a universal material testing machine at a tensile speed of 300 mm / min; according to the standard GB / T 4851-2014 Determination of adhesion performance, 1kg weight load, 70 hours without weight falling is considered passed, marked as √, otherwise it is unqualified, marked as X; hang the sample with the same size as the adhesion test in a 60℃ oven, the time for the pressure-sensitive tape to fall off the glass exceeds 2h, it is considered passed in heat resistance, marked as √, otherwise it is unqualified, marked as X; cut the polarizer pressure-sensitive adhesive into 120×240mm, stick it to the glass plate, put it in an 80℃ oven, and pass the heat aging test if there is no blistering, peeling, adhesive cracking and other appearance changes after 500h. Test, marked as √, otherwise it is unqualified and recorded as X; the glass plate with polarizer is placed at -35℃ (30 minutes) ~ 80℃ (30 minutes) for 300 cycles, and there is no significant appearance change such as bubbling, peeling, glue cracking and discoloration, which is judged to have passed the hot and cold shock test, marked as √, otherwise it is unqualified and recorded as X; the glass plate with polarizer is placed at 60℃ and 90% humidity for 500h without bubbling, peeling, glue cracking and discoloration, which is judged to have passed the wet heat aging test, marked as √, otherwise it is unqualified and recorded as X.
[0045] Based on the above formula materials and performance testing methods, some specific embodiments and comparative examples and corresponding performance test results are listed below: Embodiment 1: 52g PUA-1, 10g IBOA, 18g isooctyl acrylate, 2g MA, 6g ACMO, 12g THFA, 0.6% of the total mass of photoinitiator TPO and 2% of the total mass of antistatic agent were mixed, and the mixture was stirred evenly in the dark. The viscosity at 30°C was about 10 Pa.s. The mixture was coated on the polarizer substrate 1 with a 25-micron wire rod, covered with a 0.05-micron PET release film, and irradiated with a 1000-watt high-pressure mercury lamp. The curing energy was 1.3 J / cm 2 .
[0046] The raw material ratios of Examples 2 to 4 and Comparative Examples 1 to 3 are shown in Table 1, with 0.6% of the total mass of photoinitiator TPO and 2% of the total mass of antistatic agent added, the viscosity of the adhesive solution ranges from 3.5 Pa.s (Comparative Example 1) to 12 Pa.s (Comparative Example 2), and the UV curing method is the same as that of Example 1. Example 2 uses a polarizer substrate 2, and Examples 3 to 4 and Comparative Examples 1 to 3 all use a polarizer substrate 1.
[0047] Table 1. Properties of solvent-free UV pressure-sensitive adhesive and polarizer
[0048] The performance of the samples in Examples 1 to 3 all meet the performance requirements of the polarizer. In Example 4, because the amount of PUA used is larger than 70%, the performance of the pressure-sensitive adhesive has deteriorated, and the measured persistent adhesion and thermal aging properties are not good.
[0049] In Comparative Example 1, PUA-3 resin with lower viscosity is used, the resin amount is increased to 80%, the amount of active diluent added is small, and the glue can be applied. However, when the proportion of PUA-3 is too high, the Tg of the UV-cured pressure-sensitive adhesive is lower than -25°C, the adhesion of the pressure-sensitive adhesive is low, and the thermal aging, hot and cold cycle, and wet-heat aging of the polarizer cannot meet the requirements.
[0050] Comparative Example 2 uses high-viscosity PUA-1 resin. Because the proportion of PUA in the adhesive is small, while the proportion of active diluent is high, the Tg of the UV-cured pressure-sensitive adhesive is higher than 10°C. The performance of the pressure-sensitive adhesive is acceptable at room temperature, but the thermal aging performance of the polarizer after being bonded to the glass is poor, and the hot and cold cycle and wet heat aging resistance cannot meet the requirements.
[0051] Comparative Example 3 uses alkyl acrylate as the active diluent, and no polar acrylate diluent is added. The mechanical properties, thermal aging and thermal cycling of the UV-curable pressure-sensitive adhesive are poor, although the wet heat aging resistance passes the evaluation, indicating that polar acrylate needs to be mixed in the active diluent.
[0052] The pressure-sensitive adhesive of Example 3 was irradiated with a 1000-watt high-pressure mercury lamp with an irradiation energy of 0.65 J / cm 2 After curing, the pressure-sensitive adhesive passed the heat aging, heat cycle and wet heat aging tests, indicating that the UV curing energy of the solvent-free adhesive of the present invention is 0.6-1.5 J / cm 2 scope.
[0053] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A solvent-free UV curable pressure-sensitive adhesive for polarizer, characterized in that: The composition comprises the following components by weight percentage: Liquid polyurethane acrylate 50~70%; Active diluent 30~47%; Antistatic agent 1.5~2%; Photoinitiator 0.3-1%; The liquid polyurethane acrylate is prepared by polymerization of polyoxypropylene diol, aliphatic diisocyanate and hydroxyl-containing acrylate; The mass ratio of -OH groups in the polyoxypropylene diol to -NCO groups in the aliphatic diisocyanate is 0.5-1, and the viscosity of the liquid polyurethane acrylate is 40 Pa.s-300 Pa.s; The concentration of acrylate functional groups in the liquid polyurethane acrylate is less than 0.1 mmol / g.
2. The solvent-free UV curable pressure-sensitive adhesive according to claim 1, characterized in that: The mass ratio of -OH groups in the polyoxypropylene diol to -NCO groups in the aliphatic diisocyanate is 0.75-0.87, and the viscosity of the liquid polyurethane acrylate is 60 Pa.s-250 Pa.s.
3. The solvent-free UV curable pressure-sensitive adhesive according to claim 1, characterized in that: The concentration of acrylate functional groups in the liquid polyurethane acrylate is 0.05-0.09 mmol / g.
4. The solvent-free UV curable pressure-sensitive adhesive according to claim 1, characterized in that: The liquid polyurethane acrylate is prepared by polymerization of polyoxypropylene glycol, polytetramethylene glycol, aliphatic diisocyanate and hydroxyl-containing acrylate.
5. The solvent-free UV curable pressure-sensitive adhesive according to claim 1, characterized in that: The aliphatic diisocyanate is selected from any one of hexamethylene diisocyanate, isophorone diisocyanate and dicyclohexylmethane-4,4'-diisocyanate.
6. The solvent-free UV curable pressure-sensitive adhesive according to claim 1, characterized in that: The hydroxyl-containing acrylate is selected from any one of hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxybutyl acrylate.
7. The solvent-free UV curable pressure-sensitive adhesive according to claim 1, characterized in that: The active diluent is a monofunctional active diluent, selected from one or more of acrylate, vinyl amide and acrylamide.
8. A method for preparing the solvent-free UV curable pressure-sensitive adhesive according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: according to weight percentage, liquid polyurethane acrylate, active diluent, antistatic agent and photoinitiator are fully and evenly mixed to obtain solvent-free UV curing pressure-sensitive adhesive.
9. A polarizer, characterized in that: The invention comprises, from top to bottom, a functional layer, an upper PVA protective film, a PVA polarizer, a lower PVA protective film, a solvent-free UV curable pressure-sensitive adhesive layer as claimed in any one of claims 1 to 7, and a release film.
10. The polarizer according to claim 9, characterized in that: The functional layer includes at least one function of anti-glare function, anti-reflection function, anti-scratch function, and wide viewing angle diffusion function.
Citation Information
Patent Citations
Pressure-sensitive adhesive with excellent weather resistance, preparation method of pressure-sensitive adhesive and polaroid
CN119060682A